How do oil price changes affect inflation in Central and Eastern European countries? A wavelet-based Markov switching approach. Issue 1 (2nd January 2019) - Živkov, Dejan; Đurašković, Jasmina; Manić, Slavica
ABSTRACT: This paper investigates how oil price changes affect consumer price inflation in eleven Central and Eastern European countries. We use a wavelet-based Markov switching approach in order to distinguish between the effects at different time horizons. We find that the transmission of oil price changes to inflation is relatively low in the Central and Eastern European countries as an increase in the oil price of 100% is followed by a rise in inflation of 1–6 percentage points. The strongest impact from rising oil price on inflation is found for the longer time-horizons for most of the countries, which means that the indirect spillover effect is more intensive than the direct one. Also, the results indicate that exchange rate is not a significant factor when oil shocks are transmitted towards inflation, except in the occasions when high depreciation occurs. Slovakia and Bulgaria are the countries which experience the highest and most consistent pass-through effect throughout the observed sample, and this may be due to these countries having some of the highest oil import/GDP ratios.